Non-Classical Continuum Mechanics A Dictionary - Maugin, Gérard A.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This dictionary offers clear and reliable explanations of over 100 keywords covering the entire field of non-classical continuum mechanics and generalized mechanics, including the theory of elasticity, heat conduction, thermodynamic and electromagnetic continua, as well as applied mathematics. Every entry includes the historical background and the underlying theory, basic equations and typical applications. The reference list for each entry provides a link to the original articles and the most important in-depth theoretical works. Last but not least, ever y entry is followed by a cross-reference to other related subject entries in the dictionary.
Prerequisites -- A -- B -- C -- D -- E -- F -- G -- H -- I -- K -- L -- M -- N -- O -- P -- Q -- R. -S -- T.
Keywords: Mechanics, Applied; Solids; Materials -- Analysis; Mathematical physics; Solid Mechanics; Characterization and Analytical Technique; Mathematical Physics; Theoretical, Mathematical and Computational Physics